Communication narrative on the content of young leading - Oktaviansyah, Paisal; Prasetyo Wijiharto Tunggali, Ade Putranto (Universitas Ahmad Dahlan, 2022)
This article discusses the comedy narrative of Islamic da'wah brought by Habib Ja'far Al Hadar and the Indonesian Funny Council as figures who are well known among young people through social media platforms. The writing method used in the research of this article is a qualitative ethnographic research method and a case study, where content from the Youtube channel of Indonesian Funny Council with Habib Ja'far is the main source in this research.